2022
DOI: 10.3389/fpsyt.2022.977238
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder and depression among male undergraduate students in a Malaysian University

Abstract: IntroductionBody dysmorphic disorder (BDD) and depression have been reported to be both prevalent among young people worldwide, resulting in serious implications in their quality of life and social functioning. This is worrying especially in men where mental disorders are often overlooked and under-researched. This study aims to determine the proportion of male university students with symptoms suggestive of body dysmorphic disorder and depression, as well as their perception on their body image.MethodsIn this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the research study carried out by Arslan et al, the authors revealed that young individuals had mild depression, and practices promoting physical activity reduced the depression level [38]. In the study performed by Kang et al on depression with the participation of Malaysian young individuals, it was identi ed that the majority of the participants had moderate depression [39]. In the study conducted by Ngasa et al, on factors affecting depression in young individuals and the prevalence of depression among young individuals, it was discerned that a large majority of the young individuals successively had mild and moderate depression (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the research study carried out by Arslan et al, the authors revealed that young individuals had mild depression, and practices promoting physical activity reduced the depression level [38]. In the study performed by Kang et al on depression with the participation of Malaysian young individuals, it was identi ed that the majority of the participants had moderate depression [39]. In the study conducted by Ngasa et al, on factors affecting depression in young individuals and the prevalence of depression among young individuals, it was discerned that a large majority of the young individuals successively had mild and moderate depression (40).…”
Section: Discussionmentioning
confidence: 99%